Pelatihan Media Pembelajaran Digital Berbasis Canva bagi Guru di SDN Dogang Tanjung Pura Langkat - Rani Febriyanni; Syarifah Hidayani (Fusion: Jurnal Pengabdian kepada Masyarakat, 2025)
Learning media is anything that can be used to convey a message from the sender to the recipient, thereby stimulating students' thoughts, feelings, attention, and interest in learning. Learning media is crucial to the world of education. Amidst today's rapid technological developments, teachers are required to possess the necessary skills to master technology and its relevance to learning media in the classroom. The Canva application is one such learning technology utilized for learning media. Training on creating learning media using Canva was held to improve the skills and digital literacy of teachers at SDN 054945 Dogang Tanjung Pura Langkat. The results of this training concluded that this activity can help teachers become more proficient in using digital technology and offer a wider selection of learning media to motivate students to learn. The impact of the Canva training on learning includes teachers' knowledge of how to create more innovative learning media, make learning more creative and less monotonous, and transform learning into a fun experience.